2003
DOI: 10.1109/tbme.2003.812189
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory system for human motion analysis using a kinematic sensor: monitoring of daily physical activity in the elderly

Abstract: A new method of physical activity monitoring is presented, which is able to detect body postures (sitting, standing, and lying) and periods of walking in elderly persons using only one kinematic sensor attached to the chest. The wavelet transform, in conjunction with a simple kinematics model, was used to detect different postural transitions (PTs) and walking periods during daily physical activity. To evaluate the system, three studies were performed. The method was first tested on 11 community-dwelling elder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
486
0
9

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 680 publications
(500 citation statements)
references
References 35 publications
5
486
0
9
Order By: Relevance
“…Our proposed scores could be used in the long-term monitoring of shoulder kinematics in daily activity. By recognizing physical activity using additional sensors [9,20] it would be possible to provide a better evaluation of shoulder mobility and therefore offer a score which would be more reliable since it would be based on natural and voluntary activity of the patients. Moreover, using one sensor module on each humerus and one of the three scores, it should be possible to compare painful and healthy shoulders during daily activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our proposed scores could be used in the long-term monitoring of shoulder kinematics in daily activity. By recognizing physical activity using additional sensors [9,20] it would be possible to provide a better evaluation of shoulder mobility and therefore offer a score which would be more reliable since it would be based on natural and voluntary activity of the patients. Moreover, using one sensor module on each humerus and one of the three scores, it should be possible to compare painful and healthy shoulders during daily activity.…”
Section: Discussionmentioning
confidence: 99%
“…The accelerometers measure the gravity component, and using this feature, it is possible to measure the segment orientation when it is motionless [9]. Drift and DC components of the angular velocities were removed using wavelet transformation and considering the initial and final orientation of the segment based on the acceleration signals.…”
Section: Angles Estimationmentioning
confidence: 99%
“…The sensor consisted of two accelerometers with one gyroscope. Sitting and standing positions were identiWed by recognizing the diVerent nature of sit-to-stand and stand-to-sit transitions (NajaW et al 2003a, b). The detection of postural transitions allows the classiWcation of body postures before and after the transition, and also an analysis of the transition itself.…”
Section: Activity Monitoringmentioning
confidence: 99%
“…A BFS based gait analysis, showed that spatiotemporal gait parameters, such as walking speed, step length and the duration of bipedal stance, correspond well to the scores of older people with high and low fall-risks, based on the Tinetti score. However, the Tinetti score is much less discriminatory than the gait parameters for subjects with a moderate risk of falling (NajaW et al 2003a, b). Estimations of gait variability by means of an ambulatory system with a tri-axial accelerometer on the lower trunk, showed lower left-right, but higher vertical and forward trunk variability in frail elderly when compared to a Wt control group (Moe-Nilssen and Helbostad 2005).…”
Section: Assessment Of Balance and Gaitmentioning
confidence: 99%
“…Among them, the tri-axial accelerometers and bi-axial gyroscope have been extensively used since these sensors have a good performance with high accuracy and reproducibility despite a relatively-low price. Najafi et al [9] attached kinematic sensors to different parts of the body to monitor falls and ADL actions of the elderly.…”
Section: Introductionmentioning
confidence: 99%